Professor Wadia’s contributions to neurology and spinocerebellar ataxia type 2 - Fernando Spina Tensini; José Luiz Pedroso; Orlando G.P. Barsottini; Hélio A. G. Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT The authors present a historical review of the seminal contributions of Professor N. H. Wadia (1925-2016) to neurology, in particular, the first description of spinocerebellar ataxia type 2.